THE IMPORTANCE OF TEACHING PRESCHOOL CHILDREN TO MEASURE MAGNITUDES IN THE FORMATION OF THEIR MATHEMATICAL IMAGINATION - Muminova Gulasal Bakhodirovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article describes the importance of teaching preschool children to measure magnitudes in the formation of their mathematical imagination.